Toxicity of Vanadium, Cadmium, Chromium and Iron on the Kidney Status of Occupational Photocopier Operators at the University of Benin, Benin-City, Nigeria- A Pilot Study - Osadolor , B.H; Ezegbogu , M. O. (Nigerian Journal of Pharmaceutical and Applied Science Research, 2020)
There is conflicting information on the adverse health effects of photocopier toner powder on operators.This study aim to determine the possible nephrotoxic effects of some commercially available photocopier toners and establish the reference ranges of the selected heavy metals (vanadium, cadmium, chromium and iron) for residents of Benin City, Edo state, Nigeria. Blood samples were collected from photocopier operators and technicians resident in Benin City, Nigeria. Renal function and the levels of heavy metals of theses samples were assessed. The biochemical parameters used to evaluate renal function include: urea, creatinine and electrolytes. Heavy metals were analyzed by atomic absorption spectrophotometry, sodium and potassium ions were analyzed by flame emission photometry, urea was analyzed by the urease-betherlot method, creatinine was analyzed using the Jaffe technique while chloride and bicarbonate ions were analyzed using the Schales and Schales method and acid-base back titration respectively. Plasma levels of cadmium and iron were found to be significantly lower (P<0.01) in the test subjects relative to their controls. Urea and potassium ions were found to be significantly elevated in the test subjects relative to their controls at P<0.01. Creatinine, chromium and vanadium were also found to be elevated in test subjects relative to their controls; though these were not statistically significant at P>0.05. The results obtained from this study are suggestive of renal damage. Also, prolonged exposure to photocopier toner powder may be a risk factor for the development of iron deficiency anaemia.